Increasing Elderly Physical Activity Through the Elderly Sports Health Promotion Program "GANTARI" in Senggreng Village, Malang Regency, Indonesia - Suprobo, Nina Rini; Farah Mutiara Cita Diva; Diva Azzahra Putri Chori; Maharani Rohma Hidayanti; Hellen Arta Tri Andalini; Katmawanti, Septa; Sulistyorini, Anita (Warta LPM, 2024)
The World Health Organization (WHO) estimates that there will be an increase in the number of elderly people throughout the world. Malang Regency is one of the areas with the largest number of elderly people in East Java. This program's community service activities collaborate with partners at the Resilient Elderly School Kromoleo 1 in Senggreng Village, Sumberpucung District, Malang Regency. These older adults have several health complaints, such as diabetes, cholesterol, and gout, and the organ they complain about most is the knee area, so activities become hampered. The community service activity "GANTARI" (Gerakan Lansia Tangguh, Bugar dan Aktif) is here to increase awareness of the elderly about the importance of sports and physical activity to avoid degenerative diseases, especially diabetes mellitus. This community service activity has three stages, namely preparation, implementation and evaluation. An overview of the physical activity of the elderly was obtained through filling out the pre-test and post-test with the IPAQ questionnaire which was successfully completed by 52 senior citizens of Senggreng Village. Based on these results, there was a change in behavior and increased knowledge in the elderly of Senggreng Village after participating in the "GANTARI" activity. Therefore, the "GANTARI" community service activity has succeeded in promoting sports and physical activity to prevent the elderly from degenerative diseases, especially diabetes mellitus.